Flashcard effectiveness for second graders - Husman, Renee L. (My University, 2011)
Educators are faced with high standards for educating children. Reading and math are the foundation of education and a solid understanding in both subject areas is necessary for achievement throughout students' educational careers. Educational interventions are often necessary to aid students in falling behind academically with their peers. Home environments are not always conducive to homework completion or studying. When educators send extra instructional materials home with students, they want to make sure the materials are effective in helping the students with the instructional material. This study randomly assigned 16 students to one of two groups. One group received ten sight word flashcards for six weeks and the other group received ten subtraction math fact flashcards for six weeks. Pretests and posttests were given at the beginning and end of the six weeks in both subject areas for reading and math. Oral reading fluency was assessed using DIBELS (Dynamic Indicators of Basic Early Literacy Skills) oral reading fluency probes. Math fact retention was assessed using a 1-minute timed math subtraction fact test. A one-way analysis of covariance was conducted and the students who received sight word flashcards significantly improved over those who did not receive sight word flashcards. The students who received math subtraction fact flashcards had an average increase over the students who did not receive subtraction fact flashcards; however the change was not significant.
A Thesis submitted in partial fulfillment of the requirements for the Degree of Master of Science in Education
Keywords: Homework; Reading; Study skills; Subtraction; Fluency; Sight words; Flashcards